2007
DOI: 10.1295/polymj.pj2006276
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wormlike Pentaoxyethylene Dodecyl Ether C12E5 Micelles Containing n-Dodecanol

Abstract: ABSTRACT:Variation of characteristics of the wormlike micelles formed with the surfactant pentaoxyethylene dodecyl ether C 12 E 5 with uptake of n-dodecanol were examined by static (SLS) and dynamic light scattering (DLS) experiments. The SLS results have been analyzed with the aid of the light scattering theory for micelle solutions to yield the molar mass M w ðcÞ as a function of concentration c along with the cross-sectional diameter d of the micelle. The apparent hydrodynamic radius R H,app ðcÞ determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 37 publications
4
26
2
Order By: Relevance
“…1=2 in the range of c examined, as in the case of the previous findings for the micelles formed with single surfactant of various type, [9][10][11][12][13][14] for those formed with binary C i E j mixtures, 15,16 and the micelles containing n-dodecanol or n-octanol. [2][3][4][5][6] These results are in good correspondence with simple theoretical predictions derived from the thermodynamic treatments of multiple equilibria among micelles of various aggregation numbers. 7,[27][28][29] The increase in M w ðcÞ with increasing c is also consistent with the findings by Menge et al 30,31 for the C 12 E 5 + n-decane micelles.…”
Section: Analysis Of Sls Datasupporting
confidence: 79%
“…1=2 in the range of c examined, as in the case of the previous findings for the micelles formed with single surfactant of various type, [9][10][11][12][13][14] for those formed with binary C i E j mixtures, 15,16 and the micelles containing n-dodecanol or n-octanol. [2][3][4][5][6] These results are in good correspondence with simple theoretical predictions derived from the thermodynamic treatments of multiple equilibria among micelles of various aggregation numbers. 7,[27][28][29] The increase in M w ðcÞ with increasing c is also consistent with the findings by Menge et al 30,31 for the C 12 E 5 + n-decane micelles.…”
Section: Analysis Of Sls Datasupporting
confidence: 79%
“…A series of the data points for the latter near w d ¼ 0:028 are the results by Hellweg and von Klitzing. 67 We find that at small w d , the cloud point curve shift to lower temperatures with increasing w d and then shift to higher temperatures at larger w d in contrast to the case of the micelle solutions containing n-alcohol [31][32][33][34][35] for which the phase boundaries monotonically shift to lower temperatures as the alcohol content increases. In panel a of Figure 25, the emulsification failure boundary schematically shown by the surface enclosed by dashed and dotted lines indicates that too much n-dodecane can not be included in the C 12 E 5 micelles at any T and w d .…”
Section: Effects Of the Uptake Of N-alcohol And N-alkanementioning
confidence: 62%
“…They have shown that the apparent molar mass M app of the wormlike micelles formed in the L 1 phase increases with c in the range of small c, passing through a maximum, and then decreases with increasing c at higher c. Here, M app includes two contributions, i.e., concentration-dependent molar mass M w ðcÞ of the micelles and concentration dependent structure factor Sðc; q ¼ 0Þ (q the magnitude of scattering vector) which reflects thermodynamic interactions among micelles. We have also investigated solution properties of the wormlike micelles of various C i E j containing n-dodecanol, -octanol, and n-dodecane, [32][33][34][35][36][37] by applying the same technique as in the case of the micelles of C i E j and their mixtures described above.…”
Section: Effects Of the Uptake Of N-alcohol And N-alkanementioning
confidence: 99%
See 2 more Smart Citations